1996
DOI: 10.1159/000109669
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in Kuwait: A Three-Year Prospective Study

Abstract: To study the pattern of stroke in Kuwait, prospective data were collected from all patients admitted with first-ever stroke to our hospital over 3 years: 1989, 1992 and 1993. The primary-care registry over the same period was examined to ascertain that all cases of stroke seen by the primary-care doctors were referred to a hospital. Death certificates issued for people who died outside the hospital were also examined. The study included: clinical evaluation, computed tomography, electrocardiography, blood labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
61
6

Year Published

2001
2001
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(71 citation statements)
references
References 14 publications
4
61
6
Order By: Relevance
“…These findings are in agreement with other studies conducted in Saudi Arabia (67.8-68.4%) [16,17,18,19,20]. However, no significant difference was found between the number of male and female cases in this study.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are in agreement with other studies conducted in Saudi Arabia (67.8-68.4%) [16,17,18,19,20]. However, no significant difference was found between the number of male and female cases in this study.…”
Section: Discussionsupporting
confidence: 92%
“…Male predominance was also noted in regional and international studies conducted in Kuwait (74.7%) [19], Qatar (72.4-73%) [20,21], Yemen (62.6%) [22], Jordon (60%) [23], Germany (57.6%) [24], and China (61.6%) [25]. …”
Section: Discussionmentioning
confidence: 84%
“…Previous reports on stroke in Kuwait [11] and the Arabian Gulf Region [10,12,13,23] have focused primarily on epidemiology and risk factors. This study, however, has provided additional information on the outcome of stroke, which is particularly important in planning long- Percentages in parentheses.…”
Section: Discussionmentioning
confidence: 99%
“…Only limited information is available about the types of stroke and their risk factors in the Gulf region in general, and in Kuwait in particular [11]. There are even fewer articles on its short-and long-term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…However, only recent studies using CT have accurately identified the incidence of the major subtypes of stroke (cerebral infarction, intracerebral hemorrhage [ICH], and subarachnoid hemorrhage [SAH]). [1][2][3][4][5][6][7][8][9][10] This subtyping is clearly important because the different subtypes may have different risk factors and pathogeneses.…”
mentioning
confidence: 99%